(untitled) (Heritage, 2022)
Shortly after the occupation, by order issued on April 25, the authority of the Belgrade Police was re-established, and it was divided into three departments: Administrative, Special police and Criminal police. The Special police played a particularly important role during the occupation. Its main task was to fight against the communist movement, in which the IV Anti-Communist Department with its head of department Božidar Bećarević stood out. During the war, the Special police were remembered for the extremely cruel methods used by agents against suspicious and arrested communists, which overcame the ruthlessness of the occupation authorities. The research showed that the post-war communist historiography was very subjective when it described the attitude of the arrested communists in front of the investigators of the Anti-Communist Department. So, many of those who agreed to cooperate with agents, either under pressure from the police or out of their own interests, were deliberately ignored. On the other han, the behaviour of the investigators towards the arrested was almost without exception presented as sadistic. In fact, the research showed that there were certainly violent methods used against the arrested communists, but that the degree of cruelty differed significantly from case to case, and that more than half of those arrested were released almost immediately without cruel physical torture.